Training in vegetable production - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
The Asian Vegetable Research and Development Center (AVRDC) in Taiwan has increased its training programmes and its interaction with national programmes as a response to the greatly increasing demand for vegetables and the concern for human...